Anti-cancer activity of microbubble conjugated with Sorafenib containing liposome and IL4R-targeting peptide in kidney cancer cells: Anti-cancer effect of IL4R targeting microbubble complex - Lee, Jongsung; Park, See-Hyoung (Cellular and Molecular Biology, 2023)
Microbubble-based cancer treatment is a promising new approach that utilizes tiny gas-filled bubbles to deliver cancer drugs directly to tumor sites. This study aims to investigate the anti-cancer effect of the novel microbubble (MB) complex conjugated with sorafenib containing liposome and interleukin 4 receptor (IL4R) targeting peptide in kidney cancer cells. MBs were synthesized by using a solvent with an emulsion evaporation technique. To target kidney tumor cells, the produced MBs were conjugated with sorafenib (SOR) loaded liposomes and peptide ligands for (IL4RTP). The anti-cancer effect of the MB complex was accessed by WST-1 assay, confocal microscopy analysis, and western blotting analysis. The finally prepared IL4RTP (MB-Lipo(SOR)-IL4RTP) showed an average size of 1,600 nm. A498, a kidney cancer cell line that expresses IL4Rα strongly, had an uptake of the MB-Lipo(SOR)-IL4RTP when exposed to frequency ultrasonic energy. Additionally, MB-Lipo(SOR)-IL4RTP suppressed the growth of A498 cells in an IL4R-dependent manner. This cell proliferation assay results were validated by western blotting analysis of the signal transduction proteins such as FOXO3, phosphorylated Erk, total Erk, and p27. Taken together, these findings show that MB-Lipo(SOR)-IL4RTP exerts the effective targeting capacity for A498 kidney cancer cells via regulation of Erk phosphorylation as a promising ultrasound contrast and therapeutic agent for treating kidney cancers.